Assessment of work-related musculoskeletal morbidity, perceived causes and preventive activities practiced to reduce morbidity among brick field workers - Khanam, Najnin; Wagh, Vasant; Gaidhane, Abhay Motiramji; Quazi, Syyed Zahiruddin (Indian Journal of Community Health, 2019)
Background: Heavy load transportation, repetitive movements and abnormal posture are prevalent among brick field workers which lead to musculoskeletal morbidity. Aims & Objectives: Assessment of work-related musculoskeletal morbidity, perceived causes and preventive activities practiced by brick field workers. Material & Methods: It was a cross sectional study from July 2018 to April 2019. National Institute for Occupational Safety and Health recommendations was used to assess preventive activities practiced by workers. Results: Most common site of musculoskeletal symptoms was shoulder (82%). Lifting weight for long distance (79%), repetitive gesture (59.5%) and bending trunk for long duration (53%) were the causes of musculoskeletal morbidity. Conclusion: Majority of male workers worked in the field for six to seven days per week and minor burns among them was common comparing to female. Most of the workers perceived, lifting weight for long distance was the major cause of musculoskeletal morbidity.